Distal nail embbeding - Patricia Chang; Monica Vanesa Vásquez Acajabón (Our Dermatology Online, 2014)
Male patient, 35 years old who came to dermatological consultation due to contact dermatitis on back, during his clinical examination alterations of his digits was seen. Dermatological examination reveals a rim of tissue at the distal edge of the nail of both big toenails and thickened nails (Fig.1a - c, 2a, b). Both big toenails were removed due to ingrown nails two times. Diagnosis of distal nail embedding was done. Distal nail embedding is a rim of tissue at the distal edge of the nail. Causes can de acquired or congenital.